Infection of Endothelial Cells by Dengue Virus Induces ROS Production by Different Sources Affecting Virus Replication, Cellular Activation, Death and Vascular Permeability - Meuren, Lana Monteiro; Prestes, Elisa Beatriz; Papa, Michelle Premazzi; de Carvalho, Luiza Rachel Pinheiro; Mustafá, Yasmin Mucunã; da Costa, Leandro Silva; Da Poian, Andrea T.; Bozza, Marcelo Torres; Arruda, Luciana Barros (Frontiers in Immunology, 2022)
Exacerbated inflammatory response and altered vascular function are hallmarks of dengue disease. Reactive oxygen species (ROS) production has been associated to endothelial barrier disturbance and microvascular alteration in distinct pathological conditions. Increased ROS has been reported in in vitro models of dengue virus (DENV) infection, but its impact for endothelial cell physiology had not been fully investigated. Our group had previously demonstrated that infection of human brain microvascular endothelial cells (HBMEC) with DENV results in the activation of RNA sensors and production of proinflammatory cytokines, which culminate in cell death and endothelial permeability. Here, we evaluated the role of mitochondrial function and NADPH oxidase (NOX) activation for ROS generation in HBMEC infected by DENV and investigated whether altered cellular physiology could be a consequence of virus-induced oxidative stress. DENV-infected HBMECs showed a decrease in the maximal respiratory capacity and altered membrane potential, indicating functional mitochondrial alteration, what might be related to mtROS production. Indeed, mtROS was detected at later time points after infection. Specific inhibition of mtROS diminished virus replication, cell death, and endothelial permeability, but did not affect cytokine production. On the other hand, inhibition of NOX-associated ROS production decreased virus replication and cell death, as well as the secretion of inflammatory cytokines, including IL-6, IL-8, and CCL5. These results demonstrated that DENV replication in endothelial cells induces ROS production by different pathways, which impacts biological functions that might be relevant for dengue pathogenesis. Those data also indicate oxidative stress events as relevant therapeutical targets to avoid vascular permeability, inflammation, and neuroinvasion during DENV infection.